CQ-Bogotá : (City Quality) (2020)
Through extensive exploration for the identification of a need, the team decided to focus its efforts on the development of a solution related to environmental pollution exposure. Although the initial focus was solely on ultraviolet light with a restricted population which were taxi drivers. During the prototyping phase, the feedback gradually shifted the focus of the project to a solution that is more versatile and impactful. During the midterm evaluations of the capstone project, the killer experiment and minimum viable product, evidently indicated a more efficient solution would be technology based. Therefore, CQ Bogotá is an application that provides real time information not only regarding ultraviolet but air quality as well. This way, our product can benefit all members of large cities who commute on a daily basis. Taxi drivers continue to be a key population in the solution, however, are now included into the business model itself, resulting in both functional and financial benefit. CQ Bogotá main goal is to inform and encourage; sensitizing the population to potent environment risk and assisting in the development of personal safety habits. CQ Bogota's marketing scheme consist of multiple sources of incoming permitting its viability as an openly accessible free application. The final functional product has not been physically manufactured given the limitations during the pandemic. Nonetheless, the functionality of the device and the application has been accomplished. Finalization of the product consists in the development of an aesthetic device. CQ Bogotá hopes to improve the quality of life of those living in large urban areas through the incorporation of environmental hazard data into citizen's daily lives.